Pengancaman di Media Elektronik dalam Hukum Pidana Islam termasuk Jarimah Ta’zir - M. Dzulfikriddin (Journal of Sharia and Legal Science, 2024)
Threats are a crime. Nowadays, threats are often made through electronic media. Threats through electronic media violate the Electronic Information and Transactions Law as in the case that was decided by the judge in decision Number 796/Pid.Sus/2021/PN Jkt.Pst. The main problem raised in this study is how to analyze Islamic criminal law in criminal cases of threats through electronic media as in the judge's decision Number 796/Pid.Sus/2021/PN Jkt.Pst. The purpose of this study is to understand the act of threats through electronic media in Islamic criminal law. This research is a normative juridical research. The type of data is qualitative data. The data source is secondary data consisting of primary legal materials, secondary legal materials and tertiary legal materials. Data collection was carried out through literature studies, while data analysis was carried out descriptively. The results of the study show that threats through electronic media as in the decision of judge Number 796/Pid.Sus/2021/PN Jkt.Pst are subject to sanctions based on the provisions of the regulations in Article 29 in conjunction with Article 45 B and Article 27 paragraph (4) in conjunction with Article 45 paragraph (4) of Law Number 19 of 2016 concerning Amendments to Law 11 of 2008 concerning Information and Electronic Transactions. In Islamic criminal law, the act of threatening through electronic media is also a criminal act. In Islamic criminal law, this criminal threat is included in the category of Ta'zir crimes. The provisions of the sanctions are determined by the judge or ulil amri.